Studies on behavior and morphological changes in freshwater fish, Channa punctatus, under the exposure of untreated sewage water - Anand Mishra; Manish Kumar Dube; Harnam Singh Lodhi; Ambrina Sardar Khan (The Scientific Temper, 2025)
The presence of harmful chemical pollutants in freshwater ecosystems poses a significant environmental challenge due to their toxicity, persistence, and potential for bioaccumulation. This study aims to investigate the impact of untreated sewage water on the freshwater fish species Channa punctatus. C. punctatus (Bloch, 1793), class-Actinopterygii, order-Ophiocephaliformes, sub-order- Channoidae, family-Channidae. The primary objective is to elucidate the effects of exposure to this contaminated water on the behavioral patterns and physical characteristics of the fish. The fish were kept in untreated sewage water along with normal tap water as a control for different periods, and their reactions were closely observed. The fish showed many unusual behaviors such as losing balance, gasping for air at the surface, swimming in a confused or jerky way, rapid gill movement, restlessness, jumping, becoming very slow, and in some cases, floating at the surface before dying. In addition to these behavioral alterations, there were evident physical manifestations of damage. The fish exhibited patches on their bodies, alterations in skin pigmentation, loss of scales, a mucus covering on their bodies, unusual deposits on their skin, and clumping of the gills. These results show that C. punctatus reacts strongly to polluted water, both in behavior and appearance. Because of this, the C. punctatus can be used as a good bioindicator and can also help in monitoring the water quality.